EVALUATION OF THE PHYSICAL CONDITION OF DOMINANT PENCAK SILAT ATHLETES TAPAK SUCI ACEH TENGGARA IN 2025 - Zaini Hasan (CV Naskah Aceh, 2023)
This study aims to determine the level of physical fitness of pencak silat athletes trained by Tapak Suci Aceh Tenggara. The population in this study consisted of 12 pencak silat athletes trained by Tapak Suci Aceh Tenggara. Given the relatively small population size, the entire population was used as the research sample (total sampling). This study used a descriptive research design. Data collection techniques were conducted through tests: (1) cardiovascular endurance was measured using the Balke 15-minute run test, (2) upper and lower body muscle endurance was measured using pull-up, sit-up, and squat jump tests, (3) agility was measured using a 4x10-meter shuttle run test, (4) speed test measured using a 30-meter run test. The data was processed using statistics in the form of average values and percentages. The average results obtained in the study are as follows: (1) 15-minute Balke running test (X=54.77), categorized as moderate, (2) 1-minute pull-up test (X=13.6), categorized as good, (3) 1-minute sit-up test (X=58.75), categorized as good, (4) squat jump test (X=54.5) categorized as good, (5) 30-meter run test (X=3.97) categorized as very good, (6) medicine ball push test (X=4.94) categorized as good, (7) 4x10-meter shuttle run test (X=13.45) categorized as good. From the data analysis, it can be concluded that the dominant physical condition of the pencak silat athletes trained by Tapak Suci Aceh Tenggara in 2025 is in the good category.